Leptin Regulated ILC2 Cell through the PI3K/AKT Pathway in Allergic Rhinitis - Qingxiang Zeng; Xi Luo; Yiquan Tang; Wenlong Liu; Renzhong Luo (Hindawi Limited, 2020)
Background. Recent studies suggest that leptin is involved in Th2 response in allergic rhinitis (AR). However, the effect of leptin on type II innate lymphoid cells (ILC2s) in AR is not well characterized. Methods. Twenty-six AR patients and 20 healthy controls were enrolled. Serum leptin levels were measured, and their correlation with ILC2 and type II cytokines were analyzed using enzyme-linked immunosorbent assay (ELISA) and flow cytometry. ILC2 differentiation and cytokine production stimulated by human recombinant leptin were analyzed by real-time polymerase chain reaction (PCR) and ELISA. AR mouse models were also established to verify the effect of leptin on ILC2 cell regulation. Results. Our results showed that elevated serum leptin in AR patients was correlated with the percentage of ILC2 and the expression of type II cytokines. The recombinant leptin enhanced the expression of ILC2 cell transcription factors and type II cytokine through the PI3K/AKT pathway. The AR mice treated with leptin showed as stronger ILC2 inflammation and symptoms compared with control mice. Conclusions. Our data provide evidence that upregulation of leptin promotes ILC2 responses in AR and this process was achieved through the PI3K/AKT pathway.